The Effect of Earnings Opacity on Cost of Equity with Earnings Persistence as Moderating Variable - Dervien Listionargo Listionargo; Lia Uzliawati; Iis Ismawati (PT. EQUATOR SINAR AKADEMIA, 2022)
The purpose of this study was to determine the effect of earnings opacity as measured by earnings aggressiveness and earnings smoothing on the cost of equity with earnings persistence as a moderating variable. This research focuses on manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. The population used in this study amounted to 16 manufacturing companies using purposive sampling method based on certain criteria. This research uses associative technique with quantitative methodology. The technique used in collecting data is by using library research derived from the company's annual financial statements. The hypothesis test used is the Multiple Linear Regression Test and Moderated Regression Analysis using the SPSS 25 program. The results of this study show a significant positive effect of earnings aggressiveness on the cost of equity, earnings smoothing has a positive effect on the cost of equity but is not significant, earnings persistence is able to weaken the relationship between earnings aggressiveness and the cost of equity, and earnings persistence is not able to moderate the relationship between earnings smoothing and the cost of equity.